DIFFERENCES IN INFLUENCES BY THE SECOND ORDER THEORY DEPENDING ON MEMBERS CROSS SECTIONS - Zdravković, Slavko; Igić, Tomislav; Mijalković, Marina; Stanojev, Milovan (Journal of Applied Engineering Science, 2016)
In this paper Second order theory is derived from deformation method. In given numerical examples (1 and 2) it has been shown that for the same values of normal forces in members, for the same lengths of the members of the system and for the same modulus of elasticity E, but for the different dimensions of cross sections, very different influences are obtained. Calculated values of bending moments differ very little, if the cross section of the member system is closer to real value, than that of the cross-section of members which are closer to the system stability limit. The greater the member rigidity, the smaller the differences in influences and displacements calculated according to linearized and accurate Second order theory.